The Importance of Oxidative Stress in the Human Body in the Development of Chronic Heart Failure - Khalilova Feruza Abdujalolovna (American Journal of Biomedicine and Pharmacy, 2025)
It is known that oxidative stress plays a key role in the development of SLE and, as a result, SCD. In a state of oxidative stress, pro-inflammatory cytokines increase in the human body, leading to systemic inflammatory processes in many organs. α-tumor necrosis factor (α-O'NO), interleukin (IL)-1 and 6 take the leading place in the mentioned processes. From this point of view, it is desirable to study the relationship between oxidative stress, inflammatory cytokines and uromodulin protein.